Dynamical Critical Exponent for Two-Species Totally Asymmetric Diffusion on a Ring - Wehefritz-Kaufmann, B. (Symmetry, Integrability and Geometry: Methods and Applications, 2010)
We present a study of the two species totally asymmetric diffusion model using the Bethe ansatz. The Hamiltonian has Uq(SU(3)) symmetry. We derive the nested Bethe ansatz equations and obtain the dynamical critical exponent from the finite-size scaling properties of the eigenvalue with the smallest real part. The dynamical critical exponent is 3/2 which is the exponent corresponding to KPZ growth in the single species asymmetric diffusion model.